2021
DOI: 10.3389/fpsyt.2021.679779
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Suicide Risk Assessment Tools and Their Measured Psychometric Properties in Korea

Abstract: While there has been a slew of review studies on suicide measurement tools until now, there were not any reviews focusing on suicide assessment tools available in Korea. This review aimed to examine the psychometric properties of tools developed in Korea or the translated versions from the original tools in their foreign language and to identify potential improvements and supplements for these tools. A literature search was done using the Korean academic information search service, Research Information Service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…In a meta‐analysis evaluating the suicide risk in psychiatric patients, it was predicted that approximately half of suicides happened in lower‐risk groups (Harmer et al, 2020 ; Matthew Large et al, 2016 ). Approaches concerning sociodemographic and clinical risk factors to screening for suicide risk have predictive uncertainty with high sensitivity but lower specificity or the opposite (Baek et al, 2021 ; Belsher et al, 2019 ; Large et al, 2018 ), which is problematic. The significant associations between the predicted score and the results of clinical assessment between both attempters and nonattempters (Figure 2a ) indicated that neuroimaging had potential clinical value for the early categorization of suicidal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta‐analysis evaluating the suicide risk in psychiatric patients, it was predicted that approximately half of suicides happened in lower‐risk groups (Harmer et al, 2020 ; Matthew Large et al, 2016 ). Approaches concerning sociodemographic and clinical risk factors to screening for suicide risk have predictive uncertainty with high sensitivity but lower specificity or the opposite (Baek et al, 2021 ; Belsher et al, 2019 ; Large et al, 2018 ), which is problematic. The significant associations between the predicted score and the results of clinical assessment between both attempters and nonattempters (Figure 2a ) indicated that neuroimaging had potential clinical value for the early categorization of suicidal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There are many instruments to screen suicide risk or to predict suicide. In-Chul Baek et al have provided the list of different suicide and depression risk assessment tools in a review study [32]. Among the wide range of depression screening tools, the Beck's Scale for Suicide Ideation (BSSI) [33] and the Columbia Suicide Severity Rating Scale (C-SSRS) [34] were the most frequently carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Roy et al (2019) review studies on the various outcomes students who participate in short-term ISM programmes face and group these outcomes into broad categories related to cultural, personal and career/employment outcomes. Furthermore, the other side of the review studies has focused on ISM approaches and experiences unique to specific regions or countries (e.g., Baek et al, 2021;Bouchaib, 2023;Browne et al, 2015;Knight-Grofe & Deacon, 2016;Russell et al, 2021). Interestingly, few bibliometric reviews on the domain were recently reported (e.g., Gümüş et al, 2020;López-Duarte et al, 2021;Pham et al, 2021).…”
Section: Review Of Past Reviews On Ismmentioning
confidence: 99%